Pengaruh kualitas layanan dan store atmosphere terhadap customer loyalty - Takwim, R. Iim; Asmala, Tuti; Johan, Ahmad (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine consumer responses regarding the effect of service quality and store atmosphere on consumer loyalty at the Surjoy coffee shop in Bandung. The population in this study were true coffee consumers in the city of Bandung as many as 101 people, where the sample in this study was also the population. Data were obtained through interviews, observations, literature studies, and distributing questionnaires. Multiple linear analysis. The method used is descriptive verification with a quantitative approach. The results in this study indicate that there is an influence between store atmosphere and service quality on consumer loyalty. This result is supported by Dahmiri's research (2020) that there is a significant effect of these two variables on consumer loyalty. This study emphasizes that these two variables must be managed properly by the organization, especially when competition is increasing.